Policy in the Pipeline: Identifying Regional Public Investment Priorities Using a Natural Experiment - Michal Myck; Mateusz Najsztub (Institute of Labor Economics (IZA), 2019)
We identify regional public investment priorities by studying the development of the water pipe system in the largest district in Poland. For this purpose, we take advantage of a major administrative re-form, implemented on 1 January 1999, which substantially changed the structure of Polish local government and reduced the number of top-tier administrative regions from 49 to 16. We treat the reform as a natural experiment, and apply the difference-in-differences approach to study developments along the boundary of the new Mazovian voivodeship. We find strong and positive implications for the development of the water pipe system in municipalities within the Mazovian voivodeship compared with those just outside its boundaries. The overall post-reform difference in the length of the total water pipe network is 25% and the difference in the per-capita length of the network is 30%. Local public investment priorities at the voivodeship level, potentially related to effective use of EU funds, are the most likely determinants of these differences.
Keywords: H43; H73; P35; 330; public investment policy; water pipe system; administrative reform